A comprehensive phylogeny of flat bark beetles (Coleoptera: Cucujidae) with a revised classification and a new South American genus. (2nd March 2020) - Jin, Mengjie; Zwick, Andreas; Ślipiński, Adam; Marris, John W. M.; Thomas, Michael C.; Pang, Hong
Abstract: The phylogenetic relationships within the beetle family Cucujidae were investigated for the first time. Fifty‐seven morphological characters were used for maximum parsimony and Bayesian analyses. Mitochondrial genomes were generated from museum specimens through genome skimming and used for phylogenetic analyses in a maximum likelihood framework due to the difficulty in collecting many of the Cucujidae species and the lack of availability of ethanol‐preserved specimens. Both morphological and molecular analyses supported the monophyly of the four established genera: Cucujus Fabricius, Pediacus Shuckard, Palaestes Perty, and Platisus Erichson. They also led to the description of a new genus, Thesaurus gen.n., from South America, and the recognition of two new subfamilies, Pediacinae subfam.n. and Platisinae subfam.n. Diagnoses of Cucujidae subfamilies and genera are provided along with illustrations and keys for their identification. Phylogenetic relationships between the genera were analysed and discussed based on morphological and molecular data. Three new species were described in Thesaurus gen.n. : T. albertalleni gen . et sp.n. from Venezuela, T. zaitsevi sp.n. from Peru, and T. macclarini sp.n. from Ecuador. Illustrations and a key to species are provided. The previously unknown larvae of Palaestes and Thesaurus are illustrated and described for the first time. The Eocene fossil species, Platisus punctatus (Ramírez, Corsolini & Di Iorio), from Patagonia, Argentina, is here transferred to the genus Thesaurus . This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:BF6C58C0‐C390‐4C32‐9243‐2483B6FBE369 . Abstract : Generic relationships within Cucujidae were investigated using both morphological and molecular data. Three subfamilies were designated based on the phylogenetic results. Morphological traits were mapped back onto molecular phylogenetic topology when conflicting results were observed between two analyses. Apomorphic characters were revealed for each genus and subfamily. Thesaurus gen.n. with three new species were described from South America, and fossil records were revised accordingly. Palaestes larvae were positively confirmed for first time.